Prediction of blast furnace hearth condition: part I – a steady state simulation of hearth condition during normal operation. (15th March 2020) - Dong, X. F.; Zulli, P.
ABSTRACT: A coupled flow and refractory model (CFRM) has been upgraded to assist engineers in understanding and interpreting the measured refractory temperature distributions in the hearth of a blast furnace hearth. CFRM describes the liquid flow distribution and heat transfer in the hearth, allowing various scenarios to be simulated involving coke bed properties, extent of hearth refractory wear, etc. The model was validated through comparison between measured refractory data and corresponding model predictions for the early stages of the current BlueScope's No. 5 Blast Furnace campaign. For the current campaign, the actual range in measured pad temperature fluctuation over a short time period is shown to be well within the temperature difference expected for typical coke bed movement, i.e. between sitting and floating bed conditions. Over a longer time span, a consistent evolution of the refractory wear is suggested and this is imposed to elucidate the increase in overall hearth pad temperature.